Gardenlust : a botanical tour of the world's best new gardens - Woods, Christopher, 1953- (Timber Press, Inc., 2018)
A pictorial tour of the world's most innovative new gardens includes the Tree Museum in Rapperswil, Switzerland; the Aloe Farm in Hartbeespoort, South Africa; Ichigaya Forest in Tokyo, Japan; and Mordecai Children's Garden in Denver, Colorado.